2023
DOI: 10.1002/anie.202312053
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐induced Assembly of Copper Nanoclusters with Enhanced Electrochemical Excitation and Radiative Transition for Electrochemiluminescence**

Qian Sun,
Zhenqiang Ning,
Erli Yang
et al.

Abstract: Copper nanoclusters (CuNCs) are emerging electrochemiluminescence (ECL) emitters with unique molecule‐like electronic structures, high abundance, and low cost. However, the synthesis of CuNCs with high ECL efficiency and stability in a scalable manner remains challenging. Here, we report a facile gram‐scale approach for preparing self‐assembled CuNCs (CuNCsAssy) induced by ligands with exceptionally boosted anodic ECL and stability. Compared to the disordered aggregates that are inactive in ECL, the CuNCsAssy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…The higher oxidation current of PEI/Pdots-modified GCE in PBS than that of Pdots-modified GCE in PBS containing PEI (Figure 2B, curve c) was indicative of more effective electron transport. 35 These results demonstrated that the shortened electron transfer distance between the emitter and coreactant helped to enhance ECL emission. 36 As expected, after covalently coupling PEI to Pdots to further shorten the electron-transfer distance and accelerate the electron transfer efficiency, 27 the PEI−Pdots modified GCE showed the highest ECL intensity (10 692 au) and oxidation current (Figure 2A,B, curves d).…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The higher oxidation current of PEI/Pdots-modified GCE in PBS than that of Pdots-modified GCE in PBS containing PEI (Figure 2B, curve c) was indicative of more effective electron transport. 35 These results demonstrated that the shortened electron transfer distance between the emitter and coreactant helped to enhance ECL emission. 36 As expected, after covalently coupling PEI to Pdots to further shorten the electron-transfer distance and accelerate the electron transfer efficiency, 27 the PEI−Pdots modified GCE showed the highest ECL intensity (10 692 au) and oxidation current (Figure 2A,B, curves d).…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…When encompassing the PFBT Pdots surface with equivalent PEI via electrostatic interaction (denoted as PEI/Pdots), the ECL intensity of PEI/Pdots-modified GCE in PBS (1468 au) was higher than that of PFBT Pdots-modified GCE in the presence of equal amounts of PEI in PBS (Figure A, curves a and c). The higher oxidation current of PEI/Pdots-modified GCE in PBS than that of Pdots-modified GCE in PBS containing PEI (Figure B, curve c) was indicative of more effective electron transport . These results demonstrated that the shortened electron transfer distance between the emitter and coreactant helped to enhance ECL emission .…”
Section: Resultsmentioning
confidence: 87%
“…[15][16][17][18][19] Luminophores play an important role in ECL, and a variety of ECL luminophores, including ruthenium, luminol, nanoclusters, quantum dots, and others have been developed. [20][21][22][23][24][25][26] Among them, gold nanoclusters (Au NCs), composed of several to hundreds of gold atoms less than 3 nm in diameter, have great potential as excellent ECL luminophores because of their excellent optical properties, unique catalytic activity, and good biocompatibility. [27][28][29] However, the low efficiency and poor stability of Au NCs significantly hinder their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the high cost of precious Me NCs greatly limits their application in ECL analysis. Therefore, it is especially significant to study the ECL performance and sensing applications of nonprecious Me NCs. Recently, researchers have reported the self-assembled Cu NCs induced by ligands with exceptionally boosted anodic ECL . However, there is little research on the efficient cathode ECL emission of Cu NCs.…”
Section: Introductionmentioning
confidence: 99%